1991
DOI: 10.1111/j.1365-2311.1991.tb00236.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of larval nutrition in pre‐imaginal biasing of caste in the primitively eusocial wasp Ropalidia marginata (Hymenoptera: Vespidae)

Abstract: Abstract. When freshly eclosed females of the primitively eusocial wasp Ropalidia marginata (Lep.) are isolated, only about 50% of them build nests and lay eggs thereby suggesting a pre‐imaginal biasing of caste. Wasps that lay eggs take a very variable amount of time after eclosion to start doing so. Females eclosing from nests where larvae are fed at a relatively higher rate are more likely to become egg‐layers and are likely to take less time after eclosion to begin to lay eggs. Thus, both forms of pre‐im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…Variations in the quality and quantity of larval food can affect the weight gain, body composition, and development time of various insect larvae (Scriber & Slansky 1981;Slansky & Scriber 1982), as well as influence adult size and weight (Slansky & Gadagkar et al 1991;Harris 1995). In Sphecophaga we have shown that a main correlate of the size and type of the pupal cocoon is the age of the host at the time of oviposition (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Variations in the quality and quantity of larval food can affect the weight gain, body composition, and development time of various insect larvae (Scriber & Slansky 1981;Slansky & Scriber 1982), as well as influence adult size and weight (Slansky & Gadagkar et al 1991;Harris 1995). In Sphecophaga we have shown that a main correlate of the size and type of the pupal cocoon is the age of the host at the time of oviposition (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…As there was a positive correlation between body size and adult feeding rate even when all individuals had access to unlimited food, it may be argued that wellfed larvae developed into larger sized individuals predisposed to consume more food, which then consumed more food and developed better ovaries. Conversely, poorly fed larvae developed into smaller sized individuals predisposed to consume less food, which therefore consumed less food and had poorly developed ovaries (Gadagkar et al, 1988;Gadagkar et al, 1991). Variation in larval nutrition is thus expected to be the starting point of this cascade of events leading to variation in ovarian development that ultimately facilitates the evolution of a worker caste.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…Only about 50% of the eclosing individuals build nests and lay eggs when isolated into individual holding boxes in the laboratory and provided with ad libitum food and building material. The other half die without ever laying eggs in spite of living, on average, as long as or longer than the egg layers (Gadagkar et al, 1988;Gadagkar et al, 1990;Gadagkar et al, 1991). The advantage of experimenting with freshly eclosed female wasps maintained in isolation in the laboratory is that we may rule out or minimize the influence of such factors as social interactions, dominance, queen pheromone, etc., and attribute the observed inter-individual variation in reproductive potential to intrinsic properties of the eclosing wasps, including any effects of the larval environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both these forms of preimaginal caste bias appear to be mediated by the quantity of larval nutrition, such that individuals fed relatively well as larvae have a high probability of developing into egg layers and early reproducers. Conversely, those fed relatively poorly as larvae have a high probability of developing into non-egg-layers or late reproducers (21). The time required to attain reproductive maturity ranged from 14 to 191 days (mean ± SD = 48 + 31 days) (30) (Fig.…”
Section: Delayed Reproductive Maturationmentioning
confidence: 99%